Fas Receptor: An Overview - Hanan Rabea Nada (Dermatology, 2016)
The FAS receptor (FasR), also known as apoptosis antigen 1 (APO-1 or APT), cluster of differentiation 95 (CD95) or tumor necrosis factor receptor superfamily 6 (TNFRSF6) is a protein that in humans is encoded by the FAS gene. Engagement of the cell death surface receptor Fas by Fas ligand (FasL) results in apoptotic cell death, mediated by caspase activation. Cell death mediated via Fas/FasL interaction is important for homeostasis of different cell types. In this review, we want to highlight the role of Fas receptor in different dermatologic disorders. This would definitely help our understanding of its important role in dermatology that can open a new era in using anti-Fas biologic therapy in the future management of such disorders.